Inclined magnetic field and variable viscosity effects on bioconvection of Casson nanofluid slip flow over non linearly stretching sheet - Sarwar, Noman; Asjad, Muhammad Imran; Hussain, Sajjad; Alam, Md. Nur; İnç, Mustafa (Keai Publishing Ltd, 2022)
In pursuit of improved thermal transportation, the slip flow of Casson nanofluid is considered in the existence of an inclined magnetic field and radiative heat flux flow over a non-linear stretching sheet. The viscosity of the fluid is considered as a function of temperature along with the convective thermal boundary condition. Numerical solutions are obtained via Runge-Kutta along with the shooting technique method for the chosen boundary values prob-lem. To see the physical insights of the problem, some graphs are plotted for various flow and embedded parameters on temperature function, micro-organism distribution, velocity, and vol-ume fraction of nanoparticles. A decline is observed in the velocity and the temperature for Cas-son fluid. Thermophoresis and Brownian motion incremented the temperature profile. It is also found that thermal transportation can be enhanced in the presence of nanoparticles and the bio-convection of microorganisms. Present results are useful in the various sectors of engineering and for heat exchangers working in various technological processors. The main findings of the problem are validated and compared with those in the existing literature as a limiting case.(c) 2022 The Authors. Publishing services by Elsevier B.V. on behalf of KeAi Communications Co. Ltd. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Variable viscosity; Bioconvection; Inclined fi eld; Casson fl uid; Stretching sheet; Convective boundary; Velocity slip; Varying viscosity; Nonlinearly